Protein arginine deiminase 4 antagonizes methylglyoxal-induced histone glycation - Qingfei Zheng; Adewola Osunsade; Yael David (Nature Communications, 2020)
Protein arginine deiminase 4 (PAD4) facilitates the posttranslational citrullination of histones H3 and H4. Here, the authors provide evidence that PAD4 antagonizes histone methylglyoxal-glycation by rewriting the glycated arginine into citrulline and protecting the reactive sites from further glycation.